Answer
See graph and explanations.
![](https://gradesaver.s3.amazonaws.com/uploads/solution/7d9dbb94-bfc9-46c4-8e05-b34a5cd14567/result_image/1583785014.jpg?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250123%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250123T040948Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=6bc8d78a8119b8b1b1e7a68c37ccf045de64c8800cb07202aab3ec9ec536741f)
Work Step by Step
Step 1. Given the function $f(x)=\frac{2x^2}{x^2-1}=\frac{2x^2}{(x+1)(x-1)}$, we can identify two vertical asymptotes as $x=\pm1$
Step 2. We can find a horizontal asymptote as $y=2$
Step 3. We can find the x-intercept as $x=0$ and y-intercept as $y=0$
Step 4. The function is even because $f(-x)=f(x)$
Step 5. The signs of the function when crossing the vertical asymptotes can be found as
$...(+)...(-1)...(-)...(1)...(+)...$
Step 6. We can graph the function as shown in the figure.